Kontribusi Keharmonisan Keluarga Dan Kedisiplinan Belajar Terhadap Minat Belajar Matematika Siswa Kelas X SMA Negeri Colomadu Tahun Ajaran 2014/2015 - Fatimah, Meliana Anggraeni; , Idris Harta, M.A., Ph.D (2015)
The purpose of this study is to examine the contribution of family harmony to interest in mathematics learning, examine the discipline of learning to interest in mathematics learning, test the joint contribution of family harmony and discipline of learning to interest in mathematics learning. This research is a quantitative-correlative. The subjects of this study are 48 students majoring in science class 10th in Colomadu Senior High School. Data were collected by questionnaire and documentation, which students must fill out all statements related to the variables of this study. Data were analyzed using multiple regression analysis. The results showed that: (1) the family harmony provide a positive and significant effect on the interest in mathematics learning, (2) the discipline of learning provide a positive and significant effect on the interest in mathematics learning, (3) jointly family harmony and discipline of learning give a positive influence and significant toward interest in mathematics learning. Effective contribution given by family harmony is 23.44%, while discipline of learning give 39.10%. Relative contribution given by family harmony is 37.49%, while discipline of learning give 62.51%.